PENERAPAN MODEL PEMBELAJARAN CLASSROOM DISCUSSION BERBASIS SOCIO-SCIENTIFIC ISSUES UNTUK MENINGKATKAN LITERASI SAINS SISWA SMP PADA MATERI PEMANASAN GLOBAL - Achmad Fuad Rosyidi; Dhita Ayu Permata Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The still-low level of science literacy among students in Indonesia calls for innovation to improve it. One such approach is the use of the Socio-Scientific Issues-based Classroom Discussion learning model, which has the potential to be implemented. This study aims to describe the improvement in students’ science literacy skills after being taught using the Classroom Discussion learning model based on Socio-Scientific Issues. The study employed a pre-experimental design with a one-group pretest-posttest design. The subjects of this study were students in class VII-C at SMP Labschool Unesa 3 in Surabaya. The research instruments included an observation sheet for learning implementation, pretest and posttest science literacy questions, and a student response questionnaire. Data analysis techniques used normality tests, hypothesis tests, and N-Gain tests. The results of the normality test indicated that the data were not normally distributed. The results of the hypothesis test using the Wilcoxon test indicated that there was an effect of using the learning model. The results of the N-Gain test showed that 5.3% of students fell into the low category, 89.5% into the moderate category, and 5.3% into the high category. These results were supported by the implementation of the learning process, which achieved an average percentage of 100% per session, categorized as “very good.” Additionally, student responses to the learning process yielded a result of 83.4%, interpreted as “very positive”. It can therefore be concluded that the Classroom Discussion learning model based on socio-scientific issues can improve students’ science literacy. Suggestions for future research include the use of technology-assisted learning, the use of different controversial issues, or other research methods to improve the science literacy of junior high school students.